Clinical, surgical and postoperative outcome analysis of tumors occupying both posterior and middle cranial fossa - Singh, Rahul; Prasad, Ravi Shankar; Singh, Ramit Chandra; Singh, Kulwant; Sahu, Anurag (Nepal Journal of Neuroscience, 2021)
Objectives: To analyse clinical, surgical and postoperative outcome perspectives of tumors occupying both middle and posterior cranial fossa.Materials and Methods: This retrospective cohort study includes 23 patients operated for tumors involving both middle and posterior cranial fossa in our department between August 2016 and August 2020. Each patient was evaluated for age, sex, co morbidities, tumour histopathology, clinical presentation, radiological characteristics, surgical and outcome characteristics. Unpaired t- test and chi-square test was used for statistical analysis. P < 0.05 was considered statistically significant.Results: The mean age was 46 years (range 40–57 years), with the majority of patients being female (56.5%). Most tumors (65.3%) were trigeminal schwannoma, with the remaining being vestibular schwannoma (21.7%), facial schwannoma (8.7%) and epidermoid (4.3%). The most commonly used surgical approach was the retrosigmoid approach (30.4%) and combined approach (30.4%).  Gross total resection (GTR) was done in 14 patients while subtotal resection (STR) was done in 9 patients. STR was significantly associated (p